Analysis of imidazoles and triazoles in biological samples after MicroExtraction by packed sorbent. (1st January 2017) - Campestre, Cristina; Locatelli, Marcello; Guglielmi, Paolo; De Luca, Elisa; Bellagamba, Giuseppe; Menta, Sergio; Zengin, Gokhan; Celia, Christian; Di Marzio, Luisa; Carradori, Simone
Abstract: This paper reports the MEPS-HPLC-DAD method for the simultaneous determination of 12 azole drugs (bifonazole, butoconazole, clotrimazole, econazole, itraconazole, ketoconazole, miconazole, posaconazole, ravuconazole, terconazole, tioconazole and voriconazole) administered to treat different systemic and topical fungal infections, in biological samples. Azole drugs separation was performed in 36 min. The analytical method was validated in the ranges as follows: 0.02–5 μg mL −1 for ravuconazole; 0.2–5 μg mL −1 for terconazole; 0.05–5 μg mL −1 for the other compounds. Human plasma and urine were used as biological samples during the analysis, while benzyl-4-hydroxybenzoate was used as an internal standard. The precision (RSD%) and trueness (Bias%) values fulfill with International Guidelines requirements. To the best of our knowledge, this is the first HPLC-DAD procedure coupled to MEPS, which provides the simultaneous analysis of 12 azole drugs, available in the market, in human plasma and urine. Moreover, the method was successfully applied for the quantitative determination of two model drugs (itraconazole and miconazole) after oral administration in real samples. Graphical Abstract: